DETERMINAN YANG BERHUBUNGAN DENGAN TINDAKAN KEBERSIHAN DIRI SANTRIWATI DI PONDOK PESANTREN X JOMBANG - Putaka Mastar Purnamasari; Hario Megatsari (Universitas Airlangga, 2015)
Action of personal hygiene is one of the efforts that can be done to maintain health in Islamic boarding school environment. In the implementation there are many female students who ignore it by exchanged personal items. This research purposed to determine association knowledge and attitude as predisposing factors, towards action of personal hygiene female students which supported by infrastructure and facilities of boarding school as enabling factor, and hygiene regulation as reinforcing factor in X Jombang Islamic boarding school. This research was an analytical study with cross sectional design. The population was 90 female students then obtained 48 female students as sampling by used simple random sampling. Independent variables studied included knowledge and attitudes about personal hygiene. While the dependent variable studied the action of personal hygiene female students. Instruments used a questionnaire. Data analysis techniques performed by using the chi square test to see whether or not an association between knowledge and attitude with action of personal hygiene. Variables studied and have a relationship with action of personal hygiene female students if fulfi ll the requirement p <0.05. From the statistic test show that knowledge has any association with action of personal hygiene female students with p = 0.000 (p < 0.05) and coffi cient contingensy at 0.593. So the conclusions of this research is, there was any association between knowledge of personal hygiene with action of personal hygiene female students in X Jombang Islamic boarding school. Infrastructure and facilities was adequate and there was a regulation about hygiene in this boarding school.Keyword: predisposing, enabling, reinforcing, action of personal hygiene